2022
DOI: 10.3389/fimmu.2022.865241
|View full text |Cite|
|
Sign up to set email alerts
|

Cutaneous kinase activity correlates with treatment outcomes following PI3K delta inhibition in mice with experimental pemphigoid diseases

Abstract: Chronic blistering at the skin and/or mucous membranes, accompanied by a varying degree of inflammation, is the clinical hallmark of pemphigoid diseases that impose a major medical burden. Pemphigoid diseases are caused by autoantibodies targeting structural proteins of the epithelial basement membrane. One major pathogenic pathway of skin blistering and inflammation is activation of myeloid cells following Fc gamma receptor-dependent binding to the skin-bound immune complexes. This process requires activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
0
4
0
1
Order By: Relevance
“…To identify additional pathophysiologically relevant key molecules and inflammatory pathways suitable for pharmaceutic targeting, ex vivo skin models and mouse models of AIBD are of major relevance. [49][50][51][52]…”
Section: Requirements and Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…To identify additional pathophysiologically relevant key molecules and inflammatory pathways suitable for pharmaceutic targeting, ex vivo skin models and mouse models of AIBD are of major relevance. [49][50][51][52]…”
Section: Requirements and Perspectivesmentioning
confidence: 99%
“…For this indication, two innovative phase Ib trials with Dsg3‐specific nanoparticles and Dsg3‐specific CAAR T cells are currently ongoing. To identify additional pathophysiologically relevant key molecules and inflammatory pathways suitable for pharmaceutic targeting, ex vivo skin models and mouse models of AIBD are of major relevance 49–52 …”
Section: Therapymentioning
confidence: 99%
“…In line with previous findings, methylprednisolone as another first-line therapy for MMP, was also able to reduce the severity of skin, although not oral lesions in this mouse model. In this study, Ghorbanalipoor et al also showed that parsaclisib, a selective inhibitor of phosphoinositide 3-kinase delta (PI3Kd) significantly reduced skin and oral mucosal lesions (99,100). With regard to the characteristic symptom of scarring, typically occurring at the eyes of anti-laminin 332 MMP patients, this mouse model may also be suitable to unravel signaling pathways that contributes to this specific immunopathogenesis.…”
Section: Pathophysiology Of Anti-laminin 332 Pemphigoidmentioning
confidence: 66%
“…Für diese Indikation laufen gerade zwei innovative Phase‐Ib‐Studien mit Dsg3‐spezifischen Nanopartikeln und Dsg3‐spezifischen CAAR‐T‐Zellen. Um weitere pathophysiologisch relevante Schlüsselmoleküle und Entzündungswege zu identifizieren, die pharmakologisch angesteuert werden können, sind die Ex‐vivo ‐Haut‐ und Mausmodelle der BAID von großer Relevanz 49–52 …”
Section: Therapieunclassified